Adaptive Tax Planning and Corporate Sustainability: Evidence from Indonesia - Silalahi, Heriantonius; Han, Steven; Ihsan, Maulana Afif (Yayasan Sinergi Kawula Muda, 2025)
This study investigates the influence of financial performance indicators and Environmental, Social, and Governance (ESG) scores on tax planning practices among listed companies on the LQ45 index in Indonesia from 2018 to 2023. Tax planning, once focused solely on minimizing tax expenses, has evolved into a mechanism that supports corporate sustainability by promoting transparency, ethical governance, and long-term value creation in line with emerging regulatory frameworks. This study employs a quantitative panel data regression approach to examine how financial performance and ESG engagement influence corporate tax planning among Indonesia’s LQ45 firms. The results show that ETR, ROA, TI, and FPI significantly shape tax planning intensity, while higher ESG scores correspond to less aggressive fiscal behavior. These findings highlight a strategic shift in tax planning—from short-term cost minimization to a governance-driven approach integrating financial efficiency with ethical and sustainable corporate practices. From a policy standpoint, the findings suggest that fiscal regulations should reward firms integrating ESG principles into transparent and responsible tax behavior. For corporate managers, aligning tax planning with ESG principles can enhance long-term competitiveness and mitigate reputational risks. This research contributes to the discourse on responsible taxation and offers strategic insights for both regulators and business leaders.